14-3-3 Dysfunction in Dorsal Hippocampus CA1 (dCA1) Induces Psychomotor Behavior via a dCA1-Lateral Septum-Ventral Tegmental Area Pathway - Zhang, Jiajing; Navarrete, Meaghan; Wu, Yuying; Zhou, Yi (Frontiers in Molecular Neuroscience, 2022)
While hippocampal hyperactivity is implicated in psychosis by both human and animal studies, whether it induces hyperdopaminergic state and the underlying neural circuitry remain elusive. Previous studies established that region-specific inhibition of 14-3-3 proteins in the dorsal hippocampus CA1 (dCA1) induces schizophrenia-like behaviors in mice, including a novelty-induced locomotor hyperactivity. In this study, we showed that 14-3-3 dysfunction in the dCA1 over-activates ventral tegmental area (VTA) dopaminergic neurons, and such over-activation is necessary in eliciting psychomotor behavior in mice. We demonstrated that such hippocampal dysregulation of the VTA during psychomotor behavior is dependent on an over-activation of the lateral septum (LS), given that inhibition of the LS attenuates over-activation of dopaminergic neurons and psychomotor behavior induced by 14-3-3 inhibition in the dCA1. Moreover, 14-3-3 inhibition-induced neuronal activations within the dCA1-LS-VTA pathway and psychomotor behavior can be reproduced by direct chemogenetic activation of LS-projecting dCA1 neurons. Collectively, these results suggest that 14-3-3 dysfunction in the dCA1 results in hippocampal hyperactivation which leads to psychomotor behavior via a dCA1-LS-VTA pathway.